Demonstration of two-qubit algorithms with a superconducting quantum processor - DiCarlo, L.; Chow, J. M.; Gambetta, J. M.; Bishop, Lev S.; Johnson, B. R.; Schuster, D. I.; Majer, J.; Blais, A.; Frunzio, L.; Girvin, S. M.; Schoelkopf, R. J. (Nature (London), 2009)
Solid progress By exploiting two key aspects of quantum mechanics — the superposition and entanglement of physical states — quantum computers may eventually outperform their classical equivalents. A team based at Yale has achieved an important step towards that goal — the demonstration of the first solid-state quantum processor, which was used to execute two quantum algorithms. Quantum processors based on a few quantum bits have been demonstrated before using nuclear magnetic resonance, cold ion traps and optical systems, all of which bear little resemblance to conventional computers. This new processor is based on superconducting quantum circuits fabricated using conventional nanofabrication technology. There is still a long way to go before quantum computers can challenge the classical type. The processor is very basic, containing just two quantum bits, and operates at a fraction of a degree above absolute zero. But the chip contains all the essential features of a miniature working quantum computer and may prove scalable to more quantum bits and more complex algorithms. Quantum computers, which harness the superposition and entanglement of physical states, hold great promise for the future. Here, the demonstration of a two-qubit superconducting processor and the implementation of quantum algorithms, represents an important step in quantum computing. Quantum computers, which harness the superposition and entanglement of physical states, could outperform their classical counterparts in solving problems with technological impact—such as factoring large numbers and searching databases 1 , 2 . A quantum processor executes algorithms by applying a programmable sequence of gates to an initialized register of qubits, which coherently evolves into a final state containing the result of the computation. Building a quantum processor is challenging because of the need to meet simultaneously requirements that are in conflict: state preparation, long coherence times, universal gate operations and qubit readout. Processors based on a few qubits have been demonstrated using nuclear magnetic resonance 3 , 4 , 5 , cold ion trap 6 , 7 and optical 8 systems, but a solid-state realization has remained an outstanding challenge. Here we demonstrate a two-qubit superconducting processor and the implementation of the Grover search and Deutsch–Jozsa quantum algorithms 1 , 2 . We use a two-qubit interaction, tunable in strength by two orders of magnitude on nanosecond timescales, which is mediated by a cavity bus in a circuit quantum electrodynamics architecture 9 , 10 . This interaction allows the generation of highly entangled states with concurrence up to 94 per cent. Although this processor constitutes an important step in quantum computing with integrated circuits, continuing efforts to increase qubit coherence times, gate performance and register size will be required to fulfil the promise of a scalable technology.